2021
DOI: 10.1186/s12888-021-03429-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among Ethiopian migrant returnees who were in quarantine in the context of COVID-19: institution-based cross-sectional study

Abstract: Background In association with the novel coronavirus (SARS-CoV-2) disease 2019 (COVID-19) pandemic, many numbers of Ethiopian migrants are returning to their home country, and they are required to stay in mandatory quarantine centers. This results in severe disruptions of life routines, social isolation, and loss of freedom. Studies on psychological distress among Ethiopian migrant returnees in the context of COVID-19 are scarce. This study aimed to investigate the prevalence of psychological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…However, a few studies in other refugee setting used different scales and reported a relatively lower level of COVID-19 related anxiety and stress. For example, a cross-sectional study conducted on migrant returnees (mean age 26 years) in quarantine in Ethiopia found that 48.9% had anxiety symptoms, and more than one-third of the participants (35.6%) had encountered stress (Habtamu et al, 2021 ). Another study conducted during the COVID-19 pandemic on Bhutanese and Burmese refugees (aged 30–50 years) showed that 68.8% of the participants had stress (Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies in other refugee setting used different scales and reported a relatively lower level of COVID-19 related anxiety and stress. For example, a cross-sectional study conducted on migrant returnees (mean age 26 years) in quarantine in Ethiopia found that 48.9% had anxiety symptoms, and more than one-third of the participants (35.6%) had encountered stress (Habtamu et al, 2021 ). Another study conducted during the COVID-19 pandemic on Bhutanese and Burmese refugees (aged 30–50 years) showed that 68.8% of the participants had stress (Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Measures to contain the spread of the virus have involved lockdowns and mobility restrictions, while migrant essential workers have had to work in precarious working conditions with a high risk of infection due to limited health and safety protection measures ( 9 ). All of this appears to have been detrimental to migrants' mental health, both for those who have remained in destination countries ( 50 ) and for those who have been forced to return to their countries of origin ( 51 ). According to our results and the research on migrant health in general ( 52 , 53 ), mental health of migrant workers during COVID-19 seems to be of great interest to researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Such strategies helped them to cope with the stress and worries during the breakdown of physical ties with their homeland during the pandemic. Indeed, the pandemic has affected the mental health of people, specifically immigrants who have been found to be at an increased risk of psychological distress and reduced mental well-being both in Norway ( Harris and Sandal, 2020 ) and internationally ( Habtamu et al, 2021 ; Shen and Bartram, 2020 ; Devaraj & Patel, 2021 ).…”
Section: Findings and Discussionmentioning
confidence: 99%